Co-infection of hepatitis E virus, Clonorchis sinensis, and Escherichia coli: A case report - Zhang, Lu; Wang, Xiaohao; Zhang, Jing; Wang, Zhongrong; Cai, Dachuan (Frontiers in Cellular and Infection Microbiology, 2023)
Hepatitis E virus (HEV) is a common cause of acute hepatitis that threatens human health worldwide. With the popularization of detection technology, the reports of hepatitis E have gradually increased. Here, we present a rare case of co-infection with hepatitis E viruses, Clonorchis sinensis and Escherichia coli. A 52-year-old man was hospitalized because of fatigue, jaundice, and nausea for more than 2 weeks. Laboratory tests showed elevated bilirubin, aminotransferase (ALT), and aspartate aminotransferase (AST); HEV-IgM was positive, and HEV-RNA could be detected. Moreover, parasites were found in the biliary drainage and the biliary culture, which suggested Escherichia coli. The patient was effectively treated with praziquantel, imipenem, and hepatoprotective drugs and his clinical symptoms were relieved after 2 months; total bilirubin decreased to 85.1 μmol/L, ALT decreased to 92.4 U/L, and AST decreased to 102 U/L.